MODERN MANUFACTURING TECHNIQUES OF BILLET PISTONS FOR DIESEL ENGINE OF ACCELERATED PISTON ALUMINUM ALLOY MOLDING TICS-METHODS - I. M. Koidan; A. S. Zhuravlev (Литьë и металлургия)
Research has been conducted to determine the feasibility and availability of pistons manufacturing for forced diesel engine from special piston-alloy with Tix-structure by Tix-formation methods.